Fetomaternal outcome in patients with oligohydromnions in a tertiary hospital - Bhattacharya, Ratnaboli; S., Akshaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Oligohydramnios defined as an AFI ≤5 or maximum vertical pocket devoid of umbilical cord or fetal limbs measure <2 cm, in the presence of intact membranes is a common obstetric complication. The objective was to study the fetomaternal outcome in patients with oligohydromnios in tertiary hospital. Methods: 50 singleton live pregnancies between 34-40 weeks gestation with well-established dates with AFI 5 or less were selected for the study group. 50 singleton live pregnancies between 34-40 weeks gestation with well-established dates with AFI more than 5 were selected for the control group. Ultrasound examination was done for all women whenever they visited the hospital at/after 34 weeks of gestation. AFI was obtained sonographically. Maternal and fetal outcomes were studied in both groups. Results: Oligohydromnios is associated with increased rates of LSCS and induction of labour. The babies are more likely for NICU admissions. There was no difference in low APGAR score, congenital anamoly, perinatal deaths. Conclusions: The study concludes that oligohydromnios leads to increased LSCS, induction and NICU admissions. Once oligohydramnios is detected, patients should be put on regular fetal surveillance such as Doppler studies and NST. Timely termination of pregnancy can reduce the fetal and maternal complications and improve labour outcome.